第53次日本南極地域観測隊夏期行動報告2011-2012 - 山岸, 久雄; ヤマギシ, ヒサオ; Yamagishi, Hisao (国立極地研究所, 2016)
第53次夏隊では「南極地域第Ⅷ期6カ年計画」の第2年次として，重点研究観測での大型大気レーダー（PANSY）の増強工事，設営分野での20kW 風力発電機の建設，新汚水処理設備の設置，自然エネルギー棟の屋根パネル工事等，大きな工事が計画された．しかし，今期はリュツォ・ホルム湾沖の流氷が乱氷状態（風で吹き寄せられ積み重なった状態）となり，また湾内の海氷と積雪が例年よりも大幅に厚く，「しらせ」の砕氷航行は困難を極めた．その結果「しらせ」は昭和基地から約20km の地点で基地への接岸を断念した．「しらせ」のCH-101ヘリコプター空輸と，雪上車での氷上輸送により越冬成立に必要な物資を搬入できたが，夏作業用物資は一部しか搬入できず，大きな建設作業は中止，もしくは縮小となった．一方，野外調査では，観測隊のチャーターヘリにより当初計画の8-9割を達成することができた．「しらせ」復路では日程の遅れと困難な砕氷によりシップタイムが大幅に不足し，複数の観測項目が中止，もしくは縮小となった．一方，セール・ロンダーネ山地地学調査隊，海鷹丸の海洋観測チームは所期の成果を上げることができた． In the second year of the 6-year Japanese Antarctic Research Project Phase Ⅷ, JARE-53 planned several large operations such as the reinforcement of the atmospheric radar; PANSY; and the constructions of a 20-kW wind generator, sewage disposal facilities, and the roof of the Natural Energy Control Building. Sea ice condition in Lutzow Holm Bay were very severe this season, i.e., there was hummock ice in the pack ice area and very thick fast ice with heavy snow above. Icebreaker Shirase struggled with this severe sea ice and finally gave up to proceed at a distance of about 20km from Syowa Station. We managed to transport the necessities for overwintering observation using a CH-101 helicopter onboard Shirase, snow motors, and sledge caravans on the sea ice. However, we were only able to transport only a minimal amount of supplies, and therefore had to give up major construction work. On the other hand, field observation teams conducted 80%-90% of their research plan, owing to the high performance of the chartered small helicopter. On the return voyage, the Shirase struggled with the sea ice again, and some of the research operations were canceled because of limited ship time. On the other hand, the geomorphological and geodetic survey team at Sor-Rondane Mountains and oceanographic observation team onboard the training and research ship Umitaka-maru were able toconduct their research works as planned. departmental bulletin paper